Hankel Determinant for p-Valent Alpha-Convex Functions. (8th October 2013) - Singh, Gagandeep; Mehrok, B. S.
Abstract : The objective of the present paper is to obtain the sharp upper bound of | a p + 1 a p + 3 − a p + 2 2 | for p -valent α -convex functions of the form f ( z ) = z p + ∑ k = p + 1 ∞ a k z k in the unit disc E = z : | z | < 1 .